Pour une définition de la notion de « langue régionale » - Alain Viaut; Antoine Pascaud (Lengas)
The notion of regional language has spread for half a century, particularly in Europe, although we also find it in India where it applies to co-official territorialized languages. In Europe, especially in France, it has taken the place of reference concept. We also find it through the notion of "regional or minority language" in the Council of Europe Charter applying to languages so designated.This notion ended up integrating several meanings. Consequently, this paper attempts to take stock of the common defining features and the various properties of this notion from one country to another, from minimal meanings to others meanings that add to geographical ("regional") and demolinguistic features the properties that characterize this language in relation to other minority languages, either by the type of historicity and link to the territory, or by the legal status.